The Influence of Leadership Style on Employee Work Spirit at the Tuweley Village Office, Tolitoli Regency: Pengaruh Gaya Kepemimpinan terhadap Semangat Kerja Karyawan di Kantor Kelurahan Tuweley, Kabupaten Tolitoli - Rukmini Rukmini; Ayuwandira Ayuwandira; Edi Yanto (International Journal of Economic Entrepreneurship and Business Management, 2025)
This research aims to influence leadership style on employee morale at the Tuweley Village Office, Tolitoli Regency. This research uses a quantitative design, the data source is in the form of primary data, namely data obtained through observations, interviews, documentation and questionnaires related to this research. Simple linear regression analysis method, t test, and coefficient of determination. Based on research results which show that there is an influence of Leadership Style on Employee Work Spirit at the Tuweley Village Office, Tolitoli Regency. This can be proven from the results of the simple linear regression equation variable Y = 22.791 + 0.376 X and the constant of 22.791 is the value of the Employee Work Spirit variable when the Leadership Force variable is zero, then the Work Spirit value increases by 0.376. In the hypothesis test (test) there was a level of significance of the Leadership Style variable for Employee Work Spirit, namely that it was obtained thitung > table or 4,983 > 1,697 and tsig < 5% or 0,000 < 0.05 which showed that Leadership Style had a positive and significant effect on Employee Work Spirit at the Tuweley Village Office, Tolitoli Regency and its influence was categorized as very strong.